Educational Empowerment in Managing Means and Infrastructure on Faculty of Teacher Training and Education (FKIP) at Tanjungpura University - M. Chiar (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
Empowerment is the giving of strength to individuals or groups to be more empowered than before and has a responsibility in exercising the authority entrusted to them. Therefore, empowerment is essential for an institution as a form of enormous internal power contributing to the institution. With the empowerment, institutions are increasingly responsive to change, renewal science, and technology, especially in the field of education which continues to grow following the demands of the times. This research focuses on empowering education personnel in managing facilities and infrastructure at the Teacher Training and Education Faculty. The focus of this study is "How is the empowerment of educational staff in managing facilities and infrastructure at the Teacher Training and Education Faculty?". Based on the focus of the research, the research problems are detailed as follows: 1. What is the planning of empowering education personnel in managing facilities and infrastructure? 2. How is the implementation of the empowerment of education staff in managing facilities and infrastructure?. 3 What are the steps taken by the faculty leaders in empowering education personnel? 4. How is the evaluation of the empowerment of education personnel in managing facilities and infrastructure? 5. What are the factors that support and inhibit empowering communities against the revitalization of education?This study uses a descriptive method with a qualitative approach. The data collection tools used were interviews, observation and documentation guidelines. Based on the results of the study, it was found that empowerment planning was carried out by a team that had been formed to create a program based on the faculty's vision and mission. In implementing the empowerment of education staff the leaders coordinated, but on the other hand,  the methods used to optimize work were still conventional. Evaluation of the empowerment of education personnel is carried out still by manual process, including the reporting system: The supporting factors include; Availability of internet access and utilization of technology for monitoring. Openness in planning to evaluation. The participation of all faculties in ensuring the optimization of education staff. Dedication and totality of education staff, especially team who have been assigned for more than five years in FKIP. While the inhibiting factors include: The flow of institutional planning and organization at the university which is considered too long (less simple), most monitoring and evaluation systems still use manuals, but online (modern) reporting and evaluation systems are being prepared. Central government policies related to the procurement of facilities and infrastructure that must be submitted a maximum of two years earlier. All activities need to be planned with good predictions so that challenges for HR (Human Resources) planning. The absence of performance monitoring technology, such as CCTV as a support tool for staff control in managing facilities and infrastructure.